Scientific Publication Article Writing Training for ASN Teachers at SMP N 4 Boyolali - Meti Fatimah; Muhammad Ja'far Nashir; Nur Hidayah; Dito Haryudanto; Asyrof Abdul Baqi (Universitas Lambung Mangkurat, 2023)
The importance of continuous professional development is the development of teacher competencies, which is carried out according to needs, in stages, continuously to improve their professionalism, and one of them is by writing scientific publication articles. The scientific publication article itself is a condition for promotion or class in order to advance a teacher's career. However, the reality in the field is that teachers have difficulty writing scientific publication articles because teachers have not received in-depth assistance in writing articles, even though the government has provided some kind of coaching for teachers about writing articles. The service aims to help teachers understand the importance of writing scientific publication articles. The target in this community service was the teachers at SMP N 4 Boyolali, with 39 participants. The solutions offered are first, understanding the characteristics of the research process; second, practical training in writing scientific publication articles; and third, submitting articles through the Open Journal System. The implication of the results of this dedication, apart from holding a kind of follow-up workshop, is to conduct initial research on topics around the school.